Influence of Sand Gradation on Volumetric Weigh and Compressive Strength of Pavement Foam Mortar - Basri Doni Rinaldi; Putri Elsa Eka; Adji Bayu Martanto; Hakam Abdul (Civil and Environmental Engineering)
Foam mortar is a substitute for sub-base layers and base layers in road pavement construction on peat soil, which has the advantages of lightness, strength, and self-compacting. Sand is one of the building blocks of foam mortar. The purpose of the study was to analyze the effect of the gradation of sand on the resulting physical and mechanical properties of foam mortar (foam concrete). In this research, six gradations of sand were made (gradations of 3 sand sources and 3 gradations based on pusjatan standards) and then used in the manufacture of foam mortar and analyzed for volumetric weigh and compressive strength. Foam mortar from the six gradations of sand, it is concluded that gradation no. 6 (lower limit of pusjatan gradation) with a value of volumetric weigh is 0.97 t/m3 does not float perfectly in water, and no. 1 to 5 (gradation of 3 sand sources and 2 gradations of Pusjatan upper limit and middle) with a volumetric weigh is 0.83 t/m3 - 0.93 t/m3 floats in water. The compressive strength values of the 6 gradations are above 2000 kPa and can be used as foundation layers in road pavements.